PENGARUH PENGGUNAAN MEDIA APLIKASI CANVA TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS VIII SMP HKBP SIDORAME MEDAN - Lestari Sirait, Maya; J.Sitorus, Pontas; L.L. Saragih, Elza (Universitas Islam Sumatera Utara, 2023)
This research aims to determine the effect of using the canva application media on the explanatory text writing skills of class VIII students at HKBP Sidorame Middle School Medan T.P 2022/2023. This research uses quantitative experimental research with a two group posttest-only control design. The population in the research was all class VIII students totaling 64 students, namely class VIII-A with 32 students and VIII-B with 32 students. The data analysis techniques used were normality test, homogeneity test and hypothesis test. After conducting research for pretest and posttest experiments using the canva application media, the average score for the control class was 61.56 with a standard deviation of 10.78 and the experimental class average was 81.25 with a standard deviation of 9.60. The pre-test and post-test data prerequisite test results stated that the sample had a normal and homogeneous distribution. From the results of testing the research hypothesis, a